2013
DOI: 10.15835/buasvmcn-fst:9635
|View full text |Cite
|
Sign up to set email alerts
|

Characterisation of an Aromatic Plant-based Formula using UV-Vis Spectroscopy, LC–ESI(+)QTOF-MS and HPLC-DAD Analysis

Abstract: Abstract. It is known for a long time that seasoning/condimentary herbs have antioxidant activity and antibacterial properties, being good natural alternatives for disease prevention. The different efficiency of these plants is assigned to their bioactive molecules, stability and bioavailability. In the present study seven aromatic herbs (basil, thyme, oregano, rosemary, clove, cinnamon and sage) were investigated individually. A new product was developed using basil, thyme, oregano, rosemary, clove, cinnamon … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 14 publications
1
9
0
Order By: Relevance
“…The occurrence of UV-Vis spectroscopic around 280-330 nm indicates the existence of phenolic derivatives, at 330 nm confirms the presence of flavonoids in the crude extracts [20,21]. In the present study, the chlorophyll occurrence was confirmed in all the studied extracts of P. wightii.…”
Section: Ft-ir Analysis Of Pouzolzia Wightii Stemsupporting
confidence: 82%
“…The occurrence of UV-Vis spectroscopic around 280-330 nm indicates the existence of phenolic derivatives, at 330 nm confirms the presence of flavonoids in the crude extracts [20,21]. In the present study, the chlorophyll occurrence was confirmed in all the studied extracts of P. wightii.…”
Section: Ft-ir Analysis Of Pouzolzia Wightii Stemsupporting
confidence: 82%
“…1 shows the UV-Vis spectra obtained for the diluted extracts -dilution factor 10 and, respectively, 100) performed on the extracts identified the maxima wavelengths specific to phenolic acids at 220-280 nm, to flavonoids at 290-420 nm and chlorophylls at 600-670 nm [23]. Table 1 represents the specific absorption values for the plant extracts, as well the extraction efficiency (EF factors) calculated according to the formula described in Section 2.…”
Section: Resultsmentioning
confidence: 99%
“…The obtained results were processed using specific data analysis software (Origin Pro 8.0). The Extraction Factor (EF) was determined, considering the absorption values (A max ), multiplied with the dilution factor (DF) [23].…”
Section: Chemical Characterization Methodsmentioning
confidence: 99%
“…Normalized UV-Vis spectra of L. aestuans extract and biosynthesized silver nanoparticles (L-Ag) in water are presented in Figure 3. Absorption of spectrum of L. aestuans extract revealed bands at around 289 and 320 nm, corresponding to the magnitude of resonance delocalization (( → ( conjugative characters) in the biomolecules in the plant extract [27]. Previous report has shown that absorption band around 280 and 330 nm could be due to the presence of polyphenols (tannins) and flavonoids, respectively [27].…”
Section: Synthesis and Characterizationsmentioning
confidence: 97%